2008
DOI: 10.1177/1753193408087107
|View full text |Cite
|
Sign up to set email alerts
|

Relocation of Painful Neuromas in Zone III of the Hand and Forearm

Abstract: Painful nerves are a difficult and complex clinical problem. We describe the result of treatment by proximal relocation of 51 painful end neuromas and scarred nerves of the forearm in 33 patients. The relocated nerves included 29 superficial radial nerves, 16 lateral antebrachial cutaneous nerves, two medial cutaneous nerves and four posterior cutaneous nerves. These relocations achieved no, or only mild, pain in 100% of nerves at the original site and 94% of nerves at the relocation site. It also achieved no,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 31 publications
0
29
0
5
Order By: Relevance
“…For example, zone I neuromas can be buried in the lateral aspect of the proximal phalanx or in the dorsolateral surface of the nearest metacarpal bone, 9 zone II neuromas in the pronator quadratus muscle, 10,12,42 and zone III neuromas in the brachialis or brachioradialis muscle. 11,43 Analysis in this study revealed that neither the zone nor the involvement of digits had any impact in pain assessment or functionality.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…For example, zone I neuromas can be buried in the lateral aspect of the proximal phalanx or in the dorsolateral surface of the nearest metacarpal bone, 9 zone II neuromas in the pronator quadratus muscle, 10,12,42 and zone III neuromas in the brachialis or brachioradialis muscle. 11,43 Analysis in this study revealed that neither the zone nor the involvement of digits had any impact in pain assessment or functionality.…”
Section: Discussionmentioning
confidence: 54%
“…40 Several considerations for optimal treatment selection have been suggested, such as the location of the neuroma, classification of pain, and type of neuroma. 41 The contribution of location is arguable, as some state pain in zone III is most difficult to treat, 11 whereas others note worse results in zone I. 22 Moreover, some literature suggests different treatments should be used in different zones.…”
Section: Discussionmentioning
confidence: 99%
“…While pain questionnaires and rating scales (verbal and numeric) can assess the intensity, quality, and frequency of pain and are often used in the surgical literature, [105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120] these types of measures do not evaluate the psychosocial factors that are often associated with neuropathic pain. The European Federation of Neurological Societies has presented guidelines for the assessment of neuropathic pain; 1 a baseline assessment can be achieved with NRS, VRS, or VAS, and more in-depth assessment can include pain descriptors, temporal factors, and functional impact.…”
Section: Contextual (Psychosocial) Factorsmentioning
confidence: 99%
“…These nerves can have overlapping territories or have the ability to "invade" empty nerve territories resulting from previous injury or relocation. In a study by Atherton et al, 25 the authors relocated neuromas located in zone III of the forearm. They relocated neuromas of the superficial radial nerve, lateral antebrachial cutaneous nerve, posterior cutaneous nerve of the forearm, and medial antebrachial cutaneous nerve into the brachioradialis, brachialis, biceps, and muscle bellies slightly proximal to the injuries, respectively.…”
Section: Common Neuromas Bowler's Thumbmentioning
confidence: 96%
“…They achieved 88% good to excellent pain relief results. 18 Atherton et al 25 also studied the treatment of lateral antebrachial cutaneous nerve neuromas. In the case of isolated neuromas, the nerve can be relocated into the brachialis muscle above the elbow.…”
Section: Treatment Of Neuromasmentioning
confidence: 98%